ORA waveform-derived biomechanical parameters to distinguish normal from keratoconic eyes - Luz,Allan (2013)
PURPOSE: To evaluate the ability of the Ocular Response Analyzer (ORA; Reichert Ophthalmic Instruments, Buffalo, NY) to distinguish between normal and keratoconic eyes, by comparing pressure and waveform signal-derived parameters. METHODS: This retrospective comparative case series study included 112 patients with normal corneas and 41 patients with bilateral keratoconic eyes. One eye from each subject was randomly selected for analysis. Keratoconus diagnosis was based on clinical examinations, including Placido disk-based corneal topography and rotating Scheimpflug corneal tomography. Data from the ORA best waveform score (WS) measurements were extracted using ORA software. Corneal hysteresis (CH), corneal resistance factor (CRF), Goldman-correlated intraocular pressure (IOPg), cornea-compensated intraocular pressure (IOPcc), and 37 parameters derived from the waveform signal were analyzed. Differences in the distributions among the groups were assessed using the Mann-Whitney test. Receiver operating characteristic (ROC) curves were calculated. RESULTS: Statistically significant differences between keratoconic and normal eyes were found in all parameters (p<0.05) except IOPcc and W1. The area under the ROC curve (AUROC) was greater than 0.85 for 11 parameters, including CH (0.852) and CRF (0.895). The parameters related to the area under the waveform peak during the second and first applanations (p2area and p1area) had the best performances, with AUROCs of 0.939 and 0.929, respectively. The AUROCs for CRF, p2area, and p1area were significantly greater than that for CH. CONCLUSION: There are significant differences in biomechanical metrics between normal and keratoconic eyes. Compared with the pressure-derived parameters, corneal hysteresis and corneal resistance factor, novel waveform-derived ORA parameters provide better identification of keratoconus.